Understanding the Medieval Cyclades through landscape archaeology (8th – 12th century AD) - Roussos, Konstantinos (Journal of Greek Archaeology, 2020)
In the past few decades, the study of island environments is increasingly recognized as one of the most promising areas of research. The group of islands known today as the Cyclades is located in the south central Aegean Sea and consists of more than a hundred small and middle-sized islands and islets (Figure 1). This makes it the most numerous and complicated island group in the Aegean Archipelago. Despite the fact that research has made important steps in studying the insular societies of the Cyclades, until recently, the Medieval times, especially the period between the 8th and 12th centuries AD, was approached as one of the darkest periods in their history. However, the complexity of changes, which altered insular societies during this long period, in conjunction with the diversity of the islands, make it necessary to extend our approaches beyond the limits of the traditional historical perception. In this respect, intensive surface surveys and individual studies that adopt landscape approaches played a crucial role to revise aspects of the existing historical narrative of the Cyclades in order to broaden our knowledge on Medieval insularity.